Infertility and Anxiety among Infertile Women at IVF Treatment Centre, Lalitpur - Khyaju, Reena; Yakha, Bhim Maya; Sah, Durga Kumari; Dangol, Anamika; Pandey, Sita Kumari; Bhandari, Bhawana (Journal of Advanced Academic Research, 2023)
Background: Infertility is being a tangible problem in our society. Infertility is failure to conceive after one year of regular unprotected sexual intercourse in the absence of known reproductive pathology. Infertility and its treatment related process both can create psychological and economic crisis among the women who are receiving its treatment therefore it may result in variant level of anxiety in infertile women. The main objective of this study is to determine the level of anxiety among infertile women. Methods and Materials: All together 100 sample were taken for the study by adopting non-probability purposive sampling technique. Data was collected through direct interview by using demographic and structured questionnaire was used. Beck Anxiety Inventory scale was used as structured questionnaire. Result: Out of 100 respondents, more than half 56 % of the respondents were between ages 26-35 Years age, 28% of respondents were house makers by occupation, majority of respondents 71% were working 12 hours per day. Near to half 47.6 % respondent had the Hypothyroidism. Fifty two percent of respondent's were from 4-6 years of marriage duration followed by duration of infertility were 56 % since 3 years and 45 % are taking infertility treatment from about 1 years. Majority of respondents (59%) has low anxiety level followed by moderate anxiety (35%) and severe anxiety (6%). Conclusion: Anxiety is common in infertile women. Among the respondents, all of the participants had developed the features of anxiety but in very low level. So association could not be assessed between the socio-demographic variables and level of anxiety.